THE ROLE OF THE MIDDLE EAST INVESTMEN INITIATIVE (MEII) IN DEVELOPMENT IN THE WEST BANK, PALESTINE IN THE U.S.-PALESTINE PARTNERSHIP (UPP) FRAMEWORK - Presya Ramadhan (International Journal of Economics Management and Social Science, 2018)
This paper examines the role of Middle East Investment Initiative (MEII) in development in the West Bank, Palestine in the U.S.-Palestine Partnership (UPP) framework. Answering the question of how the role of the Middle East Investment Initiative (MEII) in development in Palestine in the US-Palestine Partnership (UPP) framework and how the contribution of Public-Private Partnership (PPP) to development in Palestine, the author's thesis statement is that amid diplomatic and territorial disputes, The Middle East Investment Initiative (MEII) as a public-private partnership becomes the main channel for collecting and channeling development assistance such as resources and private sector investment that can benefit the West Bank and bring prosperity to people Palestinians. While the private sector such as the Middle East Investment Initiative (MEII) cannot do much to address diplomacy or security issues, the private sector can play an equally important role through the contribution of resources and investment to conflict areas such as Palestine to help economic development In the West Bank, Palestine.